SEH AMONGRAGA (TOKOH MISTIK JAWA DALAM SERAT CENTHINI) - Fauzan Naif (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2016)
In Javanese literature, Serat Centhini is an extraordinary work, in the term of quantities of its pages and the varieties of its content. Serat Centhini was written from January 1814 to 1823, by a team lead by Adipati Anom Amengkunagara III, Crown Prince of Surakarta Kingdom that crowned as Sunan Paku Buwana V (1820-1823) afterwards with the members such as:1) Kiai Ngabehi Ranggasutrasno, 2) Kiai Ngabehi Yasadipura II, and 3) Kiai Sastradipura. The thickness of its manuscript is around 4200 folio pages (12 editions). The content of its text is varied; include all ngelmu and kawruh that exist in Java Island. As a suluk literature, Serat Centhini also has an Islamic soul and contains Tasawwuf or Islamic Mysticism thoughts that already blend with Javanese Mysticism, for example an explanation of Javanese "religion" that purpose is to achieve "life perfection", i.e. the unity between slave and Master (manunggaling kawula-Gusti). Explanation and secret lessons are in the dialogue between Seh Amongraga, as a Javanese Mystic chief and other personalities in that book. Seh Amongraga, a.k.a Jayengresmi, is the elder of three sons of Sunan Giri. He has talent and potency towards a mystical life and practices, shown by its qualities and characters, the stages of his life, his sermons about the four ways towards God, Martabat  Tujuh, and manunggaling kawula-Gusti. In the later stage ofhis life, Seh Amonraga is more noticeable to become a Javanese Mystic practitioner that teach the science of perfection, heterodox mysticism, that finally sentence to death by Sultan Agung, therefore could be seen as an inheritance of Syeh Siti Jenar tradition